The Effect of Using YouTube Application to Improve Students' Speaking Ability at the Tenth Grade Students of Madrasah Aliyah Hubbulwathan Duri - Muhammad Babaroza (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2025)
This research discussed the effect of using YouTube application to improve students' speaking ability at the tenth grade students of Madrasah Aliyah Hubbulwathan Duri. The approach used quantitative approach and the research design used pre-experimental. The population of this research was at the tenth grade students of Madrasah Aliyah Hubbulwathan Duri one class that consisted of 34 students. This research used total sampling consisted of one class with a sample of 34 students. The technique of data collecting used pre-test and post-test. The mean of pre-test is 58.12 and the mean of post-test is 71.71. Based on the output of pair 1, the Sig value is obtained. (2-tailed) is 0.000 < 0.05. Therefore, it can be concluded that there is a significant effect of using YouTube application to improve students’ speaking ability at the tenth grade students of Madrasah Aliyah Hubbulwathan Duri.